Transacting as art, design and architecture : a non-commercial market - Bradfield, Marsha; Cremona, Cinzia; McDonnell, Amy; Sajovic, Eva (Intellect, 2021)
A combination of practical and theoretical writing, this book chronicles the realization of #TransActing: A Market of Values, an international non-commercial popup market held at Chelsea College of Arts, coordinated by Critical Practice Research Cluster, a London-based network of artists, designers, curators and academics. 96 col. plates.